Neonatal low respiratory tract chlamydia trachomatis infection: Diagnostic and treatment management. (2019) - Jouglet, M.; Wuillaume, I.; Buchs, C.; Reix, P.; Schweitzer, C.; Coutier, L.
Abstract: Maternal infection during pregnancy by Chlamydia trachomatis (Chlamydia t. ) can result in neonatal interstitial lung disease. It remains difficult for physicians to establish this diagnosis and to select the best treatment, as there is no recommendation. In these two cases of neonatal low respiratory tract Chlamydia t. infection, we proposed successfully a diagnosis method based on Chlamydia t. determination by PCR, on any type of sampling, but more specifically on urinary and pharyngeal specimens; and a management based on oral antibiotic therapy, Josamycin 50mg/kg/day during 14 days which is commonly well accepted and not invasive.